THE EFFECT OF THICKNESS VARIATION OF BERYLLIUM TARGET TOWARD CHARACTERISTICS OF NEUTRON ENERGY SPECTRUM ON CYCLOTRONS HM-30 USING MCNP-X - Sri Yuniarti; Aris Haryadi; R Farzand Abdullatif (Indonesian Journal of Physics and Nuclear Applications, 2017)
The research about the characterization of neutron energy spectrum as the effect of thickness variation of beryllium (Be) target on HM−30 cyclotron using Monte Carlo N−Particle eXtended (MCNP−X) has been conducted. This research aims to know the characteristics of neutron energy spectrum which are the result ofed by the reaction of Be(p,n) with HM−30 cyclotron as one of BNCT facilities. Modelling and simulation have been done by using MNCP−X software, then the data obtained is arranged on a graph by using Origin 8+. The result of the simulation shows that the characteristics of neutron energy spectrum of each thickness are in the range of fast neutron energy. The thicker the Beryllium target, the more diminishing the neutron energy will be.